Some questions of perfection of legislation about a public youth policy in Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article is sanctified to the problems of legal status of young people. Here legal frameworks of public youth policy of Republic of Kazakhstan open up also. In the article the stages of becoming of legislation are distinguished in the field of public youth policy. Authors are conduct the scientific analysis of current legislation of Kazakhstan. The recommendations sent to perfection of current legislation are also produced.Key words: young people, law, public youth policy, legislation, legal status of young people, a volunteer.